Cellular cardiomyoplasty with autologous skeletal myoblasts for ischemic heart disease and heart failure - Taylor, Doris A (BioMed Central, 2001)
Cell transplantation to repair or regenerate injured myocardium is a new frontier in the treatment of cardiovascular disease. Even though it is based on many years of pre-clinical studies, much remains to be understood about this methodology, even as it progresses to the clinic. For example, controversies exist over the specific cells to be used, the dosages needed for tissue repair, how cells will affect the electrical activity of the myocardium, and even whether the cells can improve myocardial function after transplantation — all of which are briefly reviewed here. Autologous skeletal myoblasts appear to be the most well studied and best first generation cells for cardiac repair. Yet cardiocytes and, more recently, stem cells have been proposed as cell sources for this technology. Their advantages and limitations are also discussed. Although cellular cardiomyoplasty (cell transplantation for cardiac repair) shows great pre-clinical promise, its future will heavily depend on conducting carefully controlled, randomized clinical trials with appropriate endpoints. Utilizing biologically active cells provides both an opportunity for tissue repair and the potential for not yet understood outcomes. As with any frontier, many pioneers will attempt to conquer it. But also as with any frontier, there are pitfalls and consequences to be considered that may surpass those of previous endeavors. The future thus requires careful consideration and well-designed trials rather than haste. The promise for cell transplantation is too great to be spoiled by ill-designed attempts that forget to account for the biology of both the cells and the myocardium.